Practicum Model Using Gadget Facilities to Develop Students' Concept Understanding - Azka, Millati; Yulianto, Agus; Masturi, Masturi (Physics Communication, 2024)
This study discusses the utilization of gadgets used for virtual practicum in order to obtain data on students' conceptual understanding in physics subjects with electricity material. This study aims to determine the understanding of students' concepts in physics subjects. Student understanding of concepts was obtained by comparing knowledge before and after the treatment is carried out. This type of research was quantitative research, with sample of class XII MIPA MAN Kendal students. Data processing techniques used pretest data and posttest data between the experimental class and the control class. The average result of the experimental class was 0.28 with the low N-gain category and the average control class was 0.16 with the low category. However, the average N-gain in the experimental class is close to the medium category, thus the average level of understanding of the concept in the experimental class is higher than that of the control class.